Hands-On RESTful Web Services with TypeScript 3 Design and Develop Scalable RESTful APIs for Your Applications. - Araújo, Biharck Muniz (Packt Publishing Ltd, 2019)
With RESTful strategy, you can create APIs for every medium such as mobile apps, web apps, and so on. In the development world, serving data is the key ingredient to developing comprehensive applications. This book will help you achieve this with the help of RESTful APIs.